Strength Through Science: A Comprehensive Look at Resistance Training and Protein Intake in Muscle Development - Kuśmierska, Martyna; Kuśmierski, Jakub (Quality in Sport, 2024)
Introduction: Resistance training (RT) has become integral to fitness and rehabilitation, offering significant advantages in muscle growth and strength, and has been associated with a reduced risk of mortality. This study underscores the effectiveness of combining RT with increased dietary protein intake to amplify muscle hypertrophy and strength gains, highlighting RT’s role in stimulating muscle protein synthesis and the importance of protein in muscle repair and growth. Material and Methods of Research: A comprehensive literature review using databases like PubMed and Google Scholar focused on keywords related to the topic. Results: Resistance training induces a multitude of cellular and molecular changes within skeletal muscle, leading to notable outcomes such as muscle hypertrophy and strength gains. This process is facilitated by the production and release of myokines - cytokines produced by muscle fibers during contraction - and an increase in muscle protein synthesis, which are essential for muscle growth and functional improvement. The integration of a high-protein diet with a structured resistance training regimen has been shown to significantly enhance these adaptations, underscoring the vital role of nutrition in augmenting the effects of physical training. By providing the necessary amino acids for muscle repair and growth, a high-protein diet complements the mechanical stimuli from resistance training, leading to greater increases in muscle mass and strength. Conclusion: This study demonstrates that combining resistance training with a high-protein diet significantly boosts muscle hypertrophy and strength, highlighting the synergy between exercise and nutrition in enhancing muscle development and necessitating further investigation into their combined effects on various populations.